Modeling traffic conflicts for use in road safety analysis: A review of analytic methods and future directions. (March 2021) - Zheng, Lai; Sayed, Tarek; Mannering, Fred
Highlights: A comprehensive review of studies using traffic conflicts in road safety analysis is provided. Conceptual and methodological issues associated with traffic conflict modeling are discussed. Modeling methodologies of traffic conflict frequency and severity are summarized. Modeling methodologies of traffic conflict-crash relationship are summarized. Promising directions for future research are outlined and discussed. Abstract: Limitations of crash data and crash-based methods have given rise to the study of alternate measures of safety that are not predicated on the occurrence of a crash such as traffic conflicts. The popularity of these alternative safety measures will likely play a prominent role in road safety analysis in the forthcoming era of connected and autonomous vehicles because of the vast amount of real-time vehicle data that are likely to be available. While traffic conflicts and crashes share the same failure mechanism in the driving process, which allows models of crash frequency and severity to be applied to model conflict frequency and severity, modeling traffic conflicts has new challenges because of their distinct characteristics. This paper provides a comprehensive review of research studies that have used traffic conflicts as a safety measure, and to present conceptual and methodological issues associated with these studies. It is found that although substantial progress has been made in the modeling methodologies of traffic conflicts over the years, more research efforts are needed. Some promising directions for future research are outlined and discussed.